PENGARUH PEMBERIAN EKSTRAK BUAH PIDADA MERAH (Sonneratia caseolaris (L.) Engl.) TERHADAP KADAR GLUKOSA DARAH TIKUS GALUR WISTAR DIABETIK - Wendi Corlia Cahyaninglatri (2023)
ABSTRACT Diabetes Mellitus is currently a global health threat, the highest cause of death in Southeast Asia, it is necessary to look for alternative treatments, namely Red Pidada fruit is known to contain bioactive flavonoids, tannins, and anthocyanins which can be used as anti-diabetics and antioxidants. This study aimed to determine the effect of giving Red Pidada fruit extract in reducing blood glucose levels in diabetic Wistar rats. This is an experimental study using a pre-post control group design, with a sample of male Wistar rats (Rattus norvegicus) taken from PT Biofarma Bandung, 2-3 months old, and ± 200 gram body weight. In the study, the rats were divided into six groups; Group 1 was given standard feed and aquadest. Groups 2, 3, 4, 5, and 6 were given a high-fat diet for 28 days. Furthermore, the rats were fasted for 10 hours to be induced by alloxan 125 mg/kg BW intraperitoneally. After 48 hours, the blood glucose from the tails was measured using a glucometer. Group 3 was added with glibenclamide, groups 4, 5, and 6 were given Red Pidada fruit extract at doses 200, 400, and 800 mg/kg BW. Treatment was given for 14 days. One-Way Anova test showed the effectiveness of Red Pidada fruit extract in reducing blood glucose levels (p = 0.000). Bonferroni Post-Hoc test results showed that Red Pidada fruit extract at a dose of 800 mg/kg BW was almost the same as the glibenclamide treatment (p = 1.000) and was the best in reduced blood glucose to near normal value. Keywords : Blood Glucose, Diabetes Melitus, Red Pidada Fruit